Gender and Cultural Representation in the Film Yuni - Arviani, Cindy; Sikumbang , Ahmad Tamrin (Asosiasi Ide Bahasa Kepri, 2024)
The researcher took the film Yuni 2021 as research material because the film shows a life that relates to gender equality issues that occur in a community environment and shows a strong representation of patriarchal culture, namely the voices of todays women who are fighting fortheir dreams and higher education. The purpose of the researcher in taking this study is to find out how gender and culture are represented in the 2021 film “Yuni”. This research method uses a qualitative descriptive method using the semiotic approach of Charles Sanders Pierce with a triangle of meaning in the form of signs, objects, and interpretations. The film “Yuni” also features scenes that depict patriarchal culture, especially in Indonesian territory. In addition to the difference in social status between men and women, this patriarchal culture shows an obsession with control or a strong desire to control everything. This leads to a gap between men and women. This representation shows how women are seen in patriarchal culture and how the film “Yuni” seeks to portray womens struggle against patriarchal culture.